2017
DOI: 10.1111/cen3.12419
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of dermatomyositis: Autoantibody profile and muscle pathology

Abstract: Dermatomyositis (DM) is an idiopathic inflammatory myopathy, which not only affects skeletal muscle and skin, but it is also associated with arthritis/ arthralgia, interstitial lung disease and cancer. The diagnostic criteria for myositis that Bohan and Peter formulated in 1975, which are often still used now, depend on the presence of a characteristic skin rash for classification of DM; without it, a diagnosis of polymyositis is given. However, advances in understanding the etiology of idiopathic inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 106 publications
1
15
2
4
Order By: Relevance
“…Histopathological studies have revealed ischemic change due to inflammatory or non-inflammatory systemic vasculopathy, and both apoptosis of the muscle cells and amplification of inflammation mediated by type-I interferon (IFN) in JDM [1,5,12]. Pathological roles of macrophages, T cells, plasmacytoid dendritic cells (pDCs), and autoantibodies have been suggested in the development of inflammatory myositis.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…Histopathological studies have revealed ischemic change due to inflammatory or non-inflammatory systemic vasculopathy, and both apoptosis of the muscle cells and amplification of inflammation mediated by type-I interferon (IFN) in JDM [1,5,12]. Pathological roles of macrophages, T cells, plasmacytoid dendritic cells (pDCs), and autoantibodies have been suggested in the development of inflammatory myositis.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…The sensitivity and specificity for overall DM patients (respective 77% and 100%) were consistent with those in the previous study using a different cohort which revealed 71% of sensitivity and 98% of specificity , further corroborating its high potential as a pathological marker for DM. Although pathological changes of DM are generally conspicuous in perifascicular areas , myofibres with MxA overexpression were seen beyond perifascicular regions in nearly half of the DM samples positive for sarcoplasmic MxA expression, representing the value of MxA immunostaining to increase diagnostic sensitivity and accuracy. Practically, improvement of pathological diagnosis for DM without PFA is particularly important.…”
Section: Discussionmentioning
confidence: 98%
“…ASS is associated with anti‐aminoacyl transfer RNA synthetase autoantibodies and clinically with myositis, characteristic skin lesion (mechanic's hands are typical, but heliotrope rash and Gottron's signs/papules can also be seen), Raynaud phenomenon, interstitial lung disease, arthritis/arthralgia, and systemic symptom such as fever . Some of the clinical features and a pathological finding of perifascicular reinforcement of human leucocyte antigen (HLA)‐ABC [major histocompatibility complex (MHC) class I] expression on the sarcoplasm are shared with DM, yet ASS has a unique myopathological phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations